1997
DOI: 10.1029/96rs03422
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to MF radar interferometry for estimating mean winds and momentum flux

Abstract: Abstract. New techniques are applied to measured Doppler velocity and angle of arrival to estimate horizontal wind vectors, variances, and momentum fluxes, from MF radar data. The approach used to estimate mean winds was first introduced as "time domain interferometry" (TDI) by Vandepeer and Reid [1995]. In the present paper, the algorithm is refined and used with data from the Urbana MF radar, which employs a single vertical antenna beam, to obtain a monthly mean wind climatology which is compared with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…While noisier, the gray profile looks similar in form. Note that this last analysis is a version of that suggested by Thorsen et al (1997) and for this case, with a relatively narrow transmitter beam (~20°for these observations), appears to deliver a tolerable result for this difficult to measure Fig. 18 Shows a typical example of the effective receiver beam positions for the BPMF radar operating in an east (red), west (yellow), north (green), south (blue), and vertical (pink) transmitter beam sequence.…”
Section: Time Domain Interferometry (Tdi) and Hybrid Doppler Interfermentioning
confidence: 79%
See 2 more Smart Citations
“…While noisier, the gray profile looks similar in form. Note that this last analysis is a version of that suggested by Thorsen et al (1997) and for this case, with a relatively narrow transmitter beam (~20°for these observations), appears to deliver a tolerable result for this difficult to measure Fig. 18 Shows a typical example of the effective receiver beam positions for the BPMF radar operating in an east (red), west (yellow), north (green), south (blue), and vertical (pink) transmitter beam sequence.…”
Section: Time Domain Interferometry (Tdi) and Hybrid Doppler Interfermentioning
confidence: 79%
“…Thorsen et al (1997) provided a more extensive theoretical formulation for the TDI approach and considered ordinary and total least squares fitting to TDI radial velocities to derive the mean and fluctuating components of the wind field. In so doing, they extended TDI to measurements of the three-dimensional mean winds and of the Reynolds stress tensor for small MF/HF PR SA radars.…”
Section: Time Domain Interferometry (Tdi) and Hybrid Doppler Interfermentioning
confidence: 99%
See 1 more Smart Citation
“…But it is only recently that attention has been paid to estimate the errors associated with the method. The effect of geophysical noise in the measurement of momentum and heat flux has been addressed by several workers [Tao and Gardner, 1995;Thorsen et al, 1997;Gardner and Yang, 1998;Riggin et al, 2004;Dutta et al, 2005]. Kudeki and Franke [1998] showed that the dominant contribution to the uncertainty of momentum flux estimates scales as the geometric mean of the horizontal and vertical wind fluctuation variances and to obtain statistically significant measurements of momentum flux, long integration times are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The received beams were analysed with hybrid Doppler interferometry (HDI) (Holdsworth and Reid, 1998), principally to determine the radial velocities of the effective scattering centres illuminated by the radar. The methodology of Thorsen et al (1997), later re-introduced by Hocking (2005) and since extensively applied to meteor radar returns, was used to estimate components of Reynolds stress due to propagating GWs and/or turbulence in the radar resolution volume. Physically reasonable momentum flux estimates are derived from the Reynolds stress components, which are also verified using a simple radar model incorporating GW-induced wind perturbations.…”
mentioning
confidence: 99%